Small Sided Games as A Cognitive Training Approach to Improve Decision Making Skills in Futsal Players in Junior High School - Muhammad Qahthan Hadiprayitno; Tri Martini; Carsiwan (Tadulako Journal Sport Sciences And Physical Education, 2026)
Decision-making is a fundamental perceptual-cognitive skill in invasion sports, including futsal, requiring players to rapidly perceive relevant information, anticipate opponents' and teammates' movements, and select appropriate actions under spatial and temporal constraints. this study aimed to examine the effect of Small-Sided Games (SSG) on the decision-making ability of futsal extracurricular students at SMP Negeri 26 Bandung. A quantitative experimental approach employing a pretest–posttest control group design was used. Thirty students were recruited through total sampling and assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group completed a five-week SSG program (three sessions per week), whereas the control group received conventional technique-based training. Decision-making ability was assessed using the Game Performance Assessment Instrument (GPAI) and analyzed using normality, homogeneity, independent-samples t-test, and N-Gain analyses. The results revealed a significant difference between the experimental and control groups following the intervention (p < 0.001), with the experimental group achieving a moderate N-Gain score (0.63). These findings indicate that SSG provides a representative learning environment that enhances player engagement and strengthens perception–action coupling through repeated exposure to dynamic game situations. Furthermore, this study extends the application of the Ecological Dynamics framework by demonstrating that representative learning design effectively enhances decision-making not only among competitive athletes but also in non-athlete junior high school students. Therefore, SSG can be recommended as an effective game-based learning approach for physical education and school-based futsal extracurricular programs.